Impact of surface processes on the dynamics of orogenic wedges: analogue models and case studies - Malavieille, J. (TRABAJOS DE GEOLOGÍA, 2009)
In recent years attention has been paid to the major role of surface processes on the evolution of mountain belts on different time scales. In this study, sandbox experiments are used to better characterize the complex interactions between surface processes and tectonics. Models results are then applied to better analyze deformation and kinematics of recent active or ancient orogens (case studies are chosen in the Taiwan belt, the Alps and the Hercynian belt).